The effects of COVID -19 on higher education: Experiences of Family and Religious Studies final year students at Great Zimbabwe University - Mashonganyika, D.; Muyambo, T. (South African Journal of Higher Education, 2022)
An unprecedented amount of disruption to life in general and higher education in particular resulted from the unexpected onset of the Coronavirus pandemic in late 2019. In Zimbabwe, cases of infection and the first victim of the pandemic were reported when the first semester of the 2020 academic year had just started in March. There is paucity of literature, at the time of writing this article, on Zimbabwe higher education students’ experiences of COVID-19 induced online education. To fill this lacuna, this article explored the effects of COVID-19 on higher education, with special focus on Family and Religious Studies (FRS) final year students at Great Zimbabwe University (GZU). The aim was to explore level 4.2 FRS students’ experiences when they were suddenly confronted with a COVID-19 induced online education. Adopting a qualitative research design where online interviews and a questionnaire were carried out with a sample of 20 male and 22 female students, we collected the students’ experiences of the COVID-19 induced online education in the teaching and learning of FRS online, identified the students’ coping strategies in dealing with COVID-19 induced online education, and solicited from the students their recommendations for a user-friendly online education. Employing the Just-In-Time Learning theory as the lens to analyse data, the students revealed that COVID-19 has had both negative and positive impacts on higher education in a developing country set up. We argue that while students and lecturers were confronted with numerous challenges in embracing COVID-19 induced-online education, they equally benefitted from the undertaking. We recommend that the University provides an enabling online teaching and learning environment and should prioritise robust training of academic staff and students on the use of online teaching and learning platforms.